Microbial filaments in stromatolites and laminites of Balbuena III Sequence (Maastrichtian/Danian) of Yacoraite Formation in Metán-Alemania Sub-basin, Salta region, Argentina, and its palaeoenvironmental significance - Roemers-Oliveira, Eduardo; Fernandes, Luiz Alberto; Bento Freire, Ednilson; Amarante Simões, Luiz Sergio [UNESP] (FapUNIFESP (SciELO), 2015)
Salta Basin is located in the northwest of Argentina and its origin is related to an intracontinental rift which was formed during the Cretaceous and early Paleogene. It is subdivided into four sub-basins (Lomas de Olmedo - east; Sey - west; Tres Cruces - north; and Metán-Alemania - south) that were filled by sediments from the Pirgua (synrift phase), Balbuena and Santa Bárbara (both in sag phase) Subgroups. The Subgroup or Supersequence Balbuena is divided into four sequences: Balbuena I, II, III and IV, from bottom to top. This research identified microbial filaments in scanning electron microscope images from stromatolites and laminites samples of Balbuena III Sequence (Maastrichtian/Danian), Yacoraite Formation, in the Metán-Alemania Sub-basin, situated in Cabra Corral dam region, district of Coronel Moldes, Argentina. The occurrence of these filaments, identified in limestones formed in dry weather periods and deposited in the closed lake interval of the studied sequence, indicates the influence of biological activity in the formation of these rocks. The identification of microbial filaments, preserved from cyanobacteria structures, supports the palaeoenvironmental interpretation, since the occurrence of these microorganisms is limited to the photic zone and is common to stressful environments. The laminites of the studied area have been interpreted as formed in supralittoral mudflats in the vadose zone, while the stromatolites were formed in sublittoral environment, being constantly submerged. In addition to the microbialites, the Balbuena III Sequence consists of carbonates, siliciclastic and mixed facies which have been deposited in a lacustrine environment.
Keywords: Lacustrine environment; Sedimentology; SEM